2006
DOI: 10.1598/rt.59.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Developing the IRIS: Toward Situated and Valid Assessment Measures in Collaborative Professional Development and School Reform in Literacy

Abstract: This article illustrates the development and use of a situated assessment tool in the context of a collaborative (university–school district) literacy reform effort in British Columbia, Canada. The three‐year project was focused on improving literacy, including reading comprehension strategy use, among students in grades 4 through 8. It began in the 2002–2003 school year, with approximately 100 teachers and 2,500 students participating. The authors describe development of the Informal Reading Inventory of Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Qualitative studies of reader profiles also have suggested that older struggling readers have difficulty with comprehension. Rogers et al (2006) differentiated six types of readers in grades 4-8, three of which had comprehension-based issues, including students who could read fluently but had little to no comprehension, students who focused on literal information and comprehended sentence by sentence, and students who got the gist of the text but had difficulty with specific details. Finally, Dennis (2009), in a small case study of her own students, found that the majority of her sixth-grade students had issues with comprehension, not decoding.…”
Section: Qualitative Findingsmentioning
confidence: 99%
“…Qualitative studies of reader profiles also have suggested that older struggling readers have difficulty with comprehension. Rogers et al (2006) differentiated six types of readers in grades 4-8, three of which had comprehension-based issues, including students who could read fluently but had little to no comprehension, students who focused on literal information and comprehended sentence by sentence, and students who got the gist of the text but had difficulty with specific details. Finally, Dennis (2009), in a small case study of her own students, found that the majority of her sixth-grade students had issues with comprehension, not decoding.…”
Section: Qualitative Findingsmentioning
confidence: 99%
“…For other types of assessments, the procedure would be to map each of the three levels to the instruments' scoring systems. For standardized tests, students who score from a high B to an A (85th to on knowledge of individual students' progress and the use of more openended questioning and retelling formats (Rogers et al, 2006).…”
Section: Visualizing and Aggregating Multiple Assessmentsmentioning
confidence: 99%
“…It was based on years of research on promoting comprehension strategies (c.f. Rogers, Winters, & Bryan, 2006). From the conception of the project I began asking where the research might lead me, especially in other areas of my life.…”
Section: Language and Literacy Volume 11 Number 1 Spring 2009mentioning
confidence: 99%